Dynamiques de création et trajectoires d’Ateliers de transformation collectifs (ATC) dans la région Occitanie - Agnès Terrieux; Mohamed Gafsi; Ugo Fiaschi (Développement Durable et Territoires)
Collective transformation workshops (ATC) have emerged over the last thirty years to pool resources for farmers to diversify. Studies about agricultural cooperation are numerous, but those related to these new structures are relatively few. The purpose of this article is to shed light on the creation process of these collective structures and their sustainability over the time. Our analysis framework uses the theory of collective action and the concept of perenniality. We chose a qualitative methodological approach in order to carry out a retrospective analysis of 18 ATC in south-western France. The results show that, overall, there is a long-term perenniality of ATCs with a various adaptation process to structural and economic circumstances and a close attention to retain the values of cooperation. However, several trajectories have been observed, among which those of decline (disappearance) or its mutation into a individual structure. Several factors of perenniality were highlighted, such as the membership renewal, ability to anticipate, the role of the ATC role in territorial development. The contribution of this research concerns the adaptive capacity of collective action structures of producers, and the need to pay particular attention to the factors of their sustainability.